Research on the influence of maker spirit on knowledge workers’ innovative behavior - Xue, Quanxiang; Liu, Can; Zhao, Min; Jin, Hui (Frontiers in Psychology, 2023)
Motivating the innovative behavior of knowledge workers with the “maker spirit” is important for enhancing innovation efficiency. Based on the unique “maker spirit” embodied in knowledge workers in Chinese, this study comprehensively considers elements of job crafting and superiors’ developmental feedback, and uses questionnaire survey method and mathematical statistical analysis method to explore the relationship between the maker spirit and the innovative behavior of knowledge workers in order to provide theoretical support for further promoting the development of social innovation. The results of the study show that the spirit of innovation, sharing, practice and entrepreneurship in the maker spirit all have a positive contribution to innovative behavior; job crafting mediates between the spirit of innovation, sharing, practice, entrepreneurship and innovative behavior; and superiors’ developmental feedback plays a positive moderating role between the spirit of innovation, sharing, practice, entrepreneurship and job crafting.